Aplikasi Pembelajaran Interaktif Pengenalan Empat Khalifah dalam Sejarah Islam untuk Siswa SD/MI: Interactive Learning Application to Introduce the Four Caliphs in Islamic History - Achyar G. Bokingo; Virginia Tulenan; Feisy D. Kambey (Jurnal Teknik Informatika, 2022)
Abstract — In today's life, we are very attached to technology. In the field of education, technology is highly utilized for learning activities or the process of teaching and learning activities. The results of student learning are always a measure of the success of the learning process. In order to make the teaching and learning process more interesting and to increase the enthusiasm for learning of students,  designed an introduction application that is knowledge that aims to make elementary school / madrasah ibtidaiyah students understand more about Islamic history in this case the introduction to the Four Caliphs. We cannot deny that today most children do not recognize the four Caliphs in Islamic history. Knowledge of the stories of the four Caliphs is very important for the development of children who can be a view to be used as an example in daily behavior. The method used in this research is the Multimedia Development Life Cycle (MDLC) method. The test results showed that there was an increase of 58% correct answers after using the application which was previously only 23%, so it can be said that this application can increase students' knowledge about the story of the Four Caliphs. Keywords — Application; Four Caliphs; Interactive Learning; Islamic History.   Abstrak — Pada kehidupan yang sekarang ini, kita sangat lekat dengan yang namanya teknologi. Dalam bidang pendidikan, teknologi sangat dimanfaatkan untuk kegiatan pembelajaran atau proses kegiatan belajar mengajar. Hasil dari pembelajaran siswa selalu menjadi tolak ukur dalam keberhasilan proses pembelajaran. Agar proses belajar mengajar lebih menarik dan untuk meningkatkan semangat belajar para siswa, dirancang sebuah aplikasi pengenalan yang bersifat pengetahuan yang bertujuan agar para siswa SD/MI lebih memahami tentang sejarah Islam dalam hal ini Pengenalan terhadap Empat Khalifah. Tidak bisa kita pungkiri pada zaman sekarang sebagian besar anak-anak tidak mengenal ke-empat Khalifah dalam sejarah Islam ini. Pengetahuan tentang kisah-kisah ke-empat Khalifah ini sangat penting bagi perkembangan anak yang dapat menjadi pandangan untuk dijadikan contoh dalam berperilaku sehari-hari. Metode yang digunakan dalam penelitian ini ialah metode Multimedia Development Life Cycle (MDLC). Hasil pengujian menunjukkan bahwa terjadi peningkatan sebesar 58% jawaban benar setelah menggunakan aplikasi yang sebelumnya hanya sebesar 23%, sehingga dapat dikatakan aplikasi ini dapat meningkatkan pengetahuan siswa/siswi tentang Kisah Empat Khalifah. Kata Kunci — Aplikasi; Empat Khalifah; Pembelajaran Interaktif; Sejarah Islam.